UiTM Jasin Navigation system / Nur Syahirah Mohammad Ariffin - Mohammad Ariffin, Nur Syahirah (2020)
UiTM Jasin Navigation System is a system that can help user to get a bigger picture of UiTM Jasin. People often use signboard to get the direction, also by asking another people around that sometimes can lead to dead end. If they reach on that particular building, they are having trouble to search for indoor room. This system is like campus navigation that focus and specified only in UiTM Jasin campus compound. One of the function of the system is it introduces every single building on the campus to the user. The system is using mobile application as platform because it is easier to use as people nowadays use smartphone on the daily basis. For the methodology, this system is using System Development Life Cycle (SDLC) method. It is a common method used by developers to develop a system. This project is using Waterfall model life cycle as the model method. After the system is fully developed, it is ready to be tested. Some type of testing was performed on the system to test the system functionality testing and usability testing. The result of usability testing is 87.86 which is considered as grade A. It is also to detect if there is any error, bugs, or defect that need to be fixed. In the future, this system may can be enhanced by using different type of technique such as augmented reality (AR) that give user real world situation navigation or perform another type of testing to give better performance for the system.